Analysis of the Quality of Health Services on Outpatient Satisfaction at the Outpatient Clinic of Kolodale Regional Hospital, North Morowali Regency, Indonesia - Harniati; Basri, Mohammad; Syakur, Rosdiana; Pakingki, Oktavianus (Jurnal Penelitian Pendidikan IPA, 2023)
Health services have an important role in the implementation of health services in hospitals as a whole, especially nursing. Health services are considered good if the health services can create a feeling of satisfaction for each patient. Achieving a level of satisfaction with the services provided to patients, both the quality of health services and the health service system, means that patients will prefer quality health services that are quality, guaranteed, and affordable to patients, or in other words, consumers are one of the most important factors in achieving the level of satisfaction in a health service. This research aims to analyze the quality of health services on the satisfaction of outpatients at Kolonodale Hospital, North Morowali Regency. This research is a quantitative study that uses an analytical survey research method with a "cross-sectional study" design approach, sampling by accidental sampling with a sample size of 50 respondents taken from outpatients at the polyclinic. The instrument used was a test developed using a Likert scale, the data obtained was analyzed using descriptive and analytical statistical analysis, namely the chy square test with a significance level of 5 percent. The results of the research showed tangible values (p=0.000), reliability (p=0.000), responsiveness (p=0.000), assurance (p=0.000), and empathy (p=0.000) because the value Ï<Î± (0.05) so it can be said that there is a relationship between tangible, reliability, responsiveness, assurance and empathy on outpatient satisfaction in Kolonodale Regional Hospital, North Morowali Regency. Tangible and empathy variables have the strongest level of relationship with patient satisfaction. So it would be better for the hospital to provide a suggestion box, so that input from patients can be conveyed and can help improve the quality of the hospital in the future.